Analisis Gaya Kepemimpinan Kepala Desa Dalam Meningkatkan Kinerja Aparat Pemerintah Desa di Desa Tenri Pakkua Kecamatan Lappariaja Kabupaten Bone - Aras Solong; Sartika; Dzulqarnain (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2022)
This paper aims to determine the leadership style of the village head. The research method used is a qualitative approach, which is to describe the phenomena that occur in the community towards leadership styles to encourage increased performance of village officials. The results showed that basically the village head in improving the performance of his apparatus used a charismatic leadership style, liazez faire and democracy in motivating his apparatus to work better. However, in its application, it is more dominant to use a democratic leadership style to encourage village officials to be more motivated in carrying out village government tasks. This can be proven by using an example (role model), namely a leader who becomes a role model and can set an example, is positive and optimistic about realizing (vision & mission), a leader who is able to meet the needs of his subordinates in carrying out village government tasks. Furthermore, in the aspect of alignment (discipline) that is being able to work together, synergize with each other in aligning the entire organizational system and empowerment (passion), a leader must be able to create a good work environment so that the organization can run well to achieve effective and efficient goals